Uncovering National Nexus's Representations: The Case of Québec. (December 2016) - Mathieu, Félix; Laforest, Guy
Abstract: This article proposes a critical analysis of the historical and ideological process that has led to the recently‐defunct Parti québécois' (PQ) Charte de la laïcité . It shows that this legislative project, as an attempt to renew Québec's nationalism, amplified the struggles and tensions that characterize the normative source of the national nexus. More specifically, this article reveals that two carrier groups – the liberal‐pluralists, on the one hand, and the republican‐conservatives, on the other – have actively fought to get access to that normative source, trying ultimately to spread their national nexus's representations as the legitimate ones. Hence, the former group suggests an individualist‐civic view for Québec's nationalism that embraces immigrant groups, Anglo‐Québécois's minority, native peoples, and the francophone majority, while the latter suggests a collectivist‐civic view for it anchoring into French‐Canadian nationalism. Therefore, two distinct integration models are confronted, where liberal‐pluralists fought against PQ's Charter of Secularism continuing to sustain interculturalism and where republican‐conservatives nevertheless support PQ's Charter.